Investor sentiment, portfolio returns, and macroeconomic variables - Azilawati Banchit; Sazali Abidin; Sophyafadeth Lim; Fareiny Morni (Journal of Risk and Financial Management, 2020)
Investor sentiment is an important aspect of behavioural finance, which provides explanation of anomalies to the asset's intrinsic values. Sentiments can easily affect individual investors. Historically, Australia is regarded as rich in resources but poor in capital, and this motivates the paper to further study and compare the effects of investor sentiment on performance returns. Aggregate and cross-sectional effects, as well as predictive regression analysis to forecast the relationships, while controlling for the macroeconomic variables, are used by employing Consumer Confidence Index (CCI) and trade volume as sentiment proxies. Contrary to some studies with aggregate stock markets, it is discovered that in the short term, investor sentiment poses a positive impact with strong predictive power on the forecast of portfolio returns but not so much in the long run, which supports the classical theories of rational investors. In both Australian and New Zealand markets, the sentiment proxies also cannot predict the returns portfolios with dividends in the long/short portfolio and book-to-market ratio long/short portfolio.
Keywords: 330; market efficiency; anomalies; behavioural finance; consumer confidence Index (CCI); dividend per share (DPS); EMH; investment; investor sentiment; macroeconomic variables; performance measures; portfolio returns; predictive power; price earning ratio (PE); return; trade volume; unit root